Como a tecnologia pode ajudar os idosos a se comunicarem sobre temas sensíveis? - Galvão, Vinicius Ferreira; Casatti, Denise; Rodrigues, Kamila Rios da Hora (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e Web, 2025)
The rapid growth of the elderly population raises challenges for designing technologies that support not only physical health but also emotional well-being. This study investigates how digital solutions can help older adults address socially sensitive issues such as grief, family conflicts, and fears of dependence. We conducted a workshop with elderly participants, combining activities like therapeutic writing, floral arrangements, and participatory design through drawing. Qualitative analysis of participant profiles, discussions, and visual artifacts revealed recurring themes including nostalgia, family, independence, respect, and vulnerability. Findings indicate that effective technological solutions for older adults should emphasize empathy, playfulness, and “lightness” in design, fostering autonomy, intergenerational connection, and safe spaces for dialogue without judgment. This work contributes preliminary guidelines for developing inclusive technologies that address the social and emotional complexities of aging, promoting active participation and dignity in later life.